Do rising rents lead to longer commutes? A gravity model of commuting flows in Ireland. (February 2021) - Ahrens, Achim; Lyons, Sean
The classical monocentric city model suggests that property prices decrease and transport costs rise with distance to the urban centre, implying that employees face a trade-off between long commutes and high housing costs when making location decisions. Accordingly, some commuters might be forced to take on longer commutes due to rising rents in central locations. In this study, we investigate empirically whether the rental differential between employment centres and residential areas predicts changes in average commuting times. To this end, we consider a gravity model of commuting flows for Ireland over 2011–2016. We present results for Ireland and the metropolitan area of Dublin, which constitutes the largest commuting region in Ireland. The results imply that a 10% rise in rents in employment centres is associated with an up to 0.6 minute rise in one-way daily average commuting times nationally (about 2.2% of the average commute duration).